The association between psychological distress and alcohol consumption and physical activity: a population-based cohort study - Alpers, Silvia Eiken; Pallesen, Ståle; Vold, Jørn Henrik; Haug, Ellen; Lunde, Linn-Heidi; Skogen, Jens Christoffer; Mamen, Asgeir; Mæland, Silje; Fadnes, Lars Thore (Frontiers in Psychiatry, 2023)
Introduction The COVID-19 pandemic and infection control measures caused changes to daily life for most people. Heavy alcohol consumption and physical inactivity are two important behavioral risk factors for noncommunicable diseases worldwide. The COVID-19 pandemic, with its social distancing measures, home office policies, isolation, and quarantine requirements may have an impact on these factors. This three-wave longitudinal study aims to investigate if psychological distress and worries related to health and economy were associated with levels and changes in alcohol consumption and physical activity during the two first years of the COVID-19 pandemic in Norway. Methods We used data collected in April 2020, January 2021, and January 2022 from an online longitudinal population-based survey. Alcohol consumption and physical activity status were assessed at all three measuring points via the Alcohol Use Disorder Identification Test (AUDIT-C) and the International Physical Activity Questionnaire (IPAQ-SF). COVID-19-related worries, home office/study, occupational situation, age, gender, children below 18 years living at home, and psychological distress (measured with the Symptom Checklist (SCL-10)) were included as independent variables in the model. A mixed model regression was used and presented with coefficients with 95% confidence intervals (CI). Results Analysis of data from 25,708 participants demonstrates that participants with substantial symptoms of psychological distress more often reported higher alcohol consumption (1.86 units/week, CI 1.48–2.24) and lower levels of physical activity [−1,043 Metabolic Equivalents of Task (METs) per week, CI −1,257;−828] at baseline. Working/studying from home (0.37 units/week, CI 0.24–0.50) and being male (1.57 units/week, CI 1.45–1.69) were associated with higher alcohol consumption. Working/studying from home (−536 METs/week, CI −609;−463), and being older than 70 years (−503 METs/week, CI −650;−355) were related to lower levels of physical activity. The differences in activity levels between those with the highest and lowest levels of psychological distress reduced over time (239 METs/week, CI 67;412), and similarly the differences in alcohol intake reduced over time among those having and not having children < 18 years (0.10 units/week, CI 0.01–0.19). Conclusion These findings highlight the substantial increases in risks related to inactivity and alcohol consumption among those with high levels of psychological distress symptoms, and particularly during the COVID-19 pandemic, and increase the understanding of factors associated with worries and health behavior.